1984
DOI: 10.1021/np50034a026
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Brickellia glutinosa

Abstract: In a continuation of a phytochemical investigation of the genus Brickellia (Tribe Eupatorieae, Subtribe Alomiinae, Family Compositae) (1-6), we now report the isolation and characterization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many flavonoids are recognized as aldose reductase inhibitors; this enzyme converts D‐glycose and D‐galactose into sorbitol and is of great importance in the diabetic and galactosemic cataract . Few studies can be found concerning sulfated flavonoids.…”
Section: Emerging Bioactive Sulfated Phenolic Small Moleculesmentioning
confidence: 99%
“…Many flavonoids are recognized as aldose reductase inhibitors; this enzyme converts D‐glycose and D‐galactose into sorbitol and is of great importance in the diabetic and galactosemic cataract . Few studies can be found concerning sulfated flavonoids.…”
Section: Emerging Bioactive Sulfated Phenolic Small Moleculesmentioning
confidence: 99%
“…Inhibition of aldose reductase has been shown to reverse these biochemical changes and has proven effective in delaying and even preventing several diabetic complications (Yabe-Nishimura 1998). During the last three decades, a variety of structurally diverse compounds have been reported to have aldose reductase inhibitory activity in-vitro against rat or bovine lens aldose reductases; these include¯avonoids (Varma 1986), hydantoin derivatives (Varma & Kinoshita 1976), oxazoline-1-acetic acid derivatives (Inagaki et al 1982), pyrimidine acetic acid derivatives (DeRuiter et al 1986), quinazoline acetic acid derivatives (Ellingboe et al 1990) and extracts of natural products (Goodwin et al 1984;Terashima et al 1990;Malamas & Miller 1991). Table 1 lists some aldose reductase inhibitors (ARIs) that have been tested in clinical trials; none is being marketed either because of side-effects (Spielberg et al 1991) or because of the lack of appreciable clinical effect (Engerman & Kern 1993).…”
mentioning
confidence: 99%